Reference data for BabyBody‐plethysmographic measurements in Chinese neonates and infants. Issue 8 (16th June 2017) - Jiang, Gaoli; Li, Albert; Wang, Libo; Qian, Liling; Cao, Yun; Huang, Jianfeng; Wan, Chengzhou; Zhang, Xiaobo
ABSTRACT: Background and objective: Population‐specific pulmonary function reference data are essential to identify the nature and severity of respiratory diseases. However, there is a lack of reference data for Chinese neonates and infants. The objective of this study was to develop reference data for tidal breathing and plethysmographic measurements for Chinese subjects during the first 2 years of life. Methods: Data of tidal breathing and plethysmography from healthy Chinese neonates (≤28 days) and infants (1–24 months) using the Jaeger MasterScreen BabyBody were collated. All subjects were sedated for the tests. Multivariable analyses were performed to determine predictive variables for the pulmonary function parameters. Reference equations for outcomes were constructed using multilevel modelling and the LMS (lambda–mu–sigma) method was used for establishing smoothed reference percentiles. Results: Four hundred and ten healthy subjects were tested. Acceptable measurements of tidal breathing analysis and plethysmography outcomes were obtained in 396 (96.6%) and 370 (90.4%) subjects, respectively. Normal reference percentiles and equations for the main parameters of tidal breathing and plethysmography were derived from test occasions of 211 neonates and 185 infants. Body weight, crown–heel length and age were significantly associated with lung function, of which length was the strongest predictor. Conclusion: This study provides reference data of BabyBody‐plethysmographic measurements for healthy Chinese subjects in their first 2 years of life. Weight and length are the strongest predictors for neonatal and infant lung function, respectively. Abstract : This is the first description of pulmonary function in healthy Chinese neonates and infants. Pulmonary function in Chinese differs to those of European descent and therefore population‐appropriate reference data are important.